Batman, year two - Barr, Mike W. 1952- (DC Comics, 2017)
"With only a year's experience as Gotham City's new protector, Batman must now confront a nightmare out of the past...a distorted reflection of himself called the Reaper, who hunted Gotham's criminals a generation earlier. His methods were harsh and cruel, and violent in the extreme. Now, just as a new breed of criminal is rising, the Reaper has returned to deal out his savage brand of justice. And the only way for Batman to stop this death-dealing vigilante is to forge an alliance with the man who destroyed his life...his own parents' murderer. But can the Dark Knight stand to confront the secret of their deaths? Or will the Reaper's revelations finally cost him his sanity?"
"Batman created by Bob Kane". - Originally published in single magazine form in Detective comics 575-578 (1987), Batman: full circle (1991)
Keywords: Batman -- Fiktive Gestalt; Superheld; Comic